Psoriasis patients' preference for an aerosol foam topical formulation. (3rd May 2018) - Vender, R.; Gooderham, M.J.; Guenther, L.C.; Kyritsis, D.; Rao, J.; Kowalczyk, A.; Ashkenas, J.
Abstract : Linked article: This article is commentary on by C‐H. Hong et al., pp. e401–e402 in this issue. To view this article visithttps://doi.org/10.1111/jdv.14985